2015
DOI: 10.3168/jds.2014-8872
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the DGAT1 K232A genotype of dairy cows on the milk metabolome and proteome

Abstract: Diglyceride O-acyltransferase 1 (DGAT1) is the enzyme that catalyzes the synthesis of triglycerides from diglycerides and acyl-coenzyme A. The DGAT1 K232A polymorphism was previously shown to have a significant influence on bovine milk production characteristics (milk yield, protein content, fat content, and fatty acid composition). The mechanism of this influence has, however, not been elucidated. In this study, metabolomics ((1)H-nuclear magnetic resonance) and proteomics (laser chromatography-tandem mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 32 publications
0
21
0
2
Order By: Relevance
“…18,19 However, in humans only a single family has been reported associated with DGAT1 mutations. Haas et al described a non-consanguineous AshkenaziJewish family in which two of three siblings were homozygous for a splice site mutation leading to exon 8 deletion associated with PLE, hypoalbuminemia, and early-onset diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, in humans only a single family has been reported associated with DGAT1 mutations. Haas et al described a non-consanguineous AshkenaziJewish family in which two of three siblings were homozygous for a splice site mutation leading to exon 8 deletion associated with PLE, hypoalbuminemia, and early-onset diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Duchemin et al (2013) reported an increase in milk C14:1 cis-9, C16:1 cis-9, and total SFA, and a decrease in total milk UFA for the DGAT1 K allele. Furthermore, according to Van Arendonk et al 2009, Lu et al (2015), and Bovenhuis et al (2016), the DGAT1 K allele is associated with increased contents of C15:0 and C17:0 in milk.…”
Section: Lactation Performance and Milk Fatty Acid Profilementioning
confidence: 95%
“…These results are largely in agreement with data in the literature. According to Schennink et al (2007), Van Arendonk et al (2009, Duchemin et al (2013), and Bovenhuis et al (2016), the DGAT1 K allele is associated with a larger fraction of C16:0, and smaller fractions of C14:0 (also reported by Lu et al, 2015), and C18 UFA in milk. In addition, Duchemin et al (2013) reported an increase in milk C14:1 cis-9, C16:1 cis-9, and total SFA, and a decrease in total milk UFA for the DGAT1 K allele.…”
Section: Lactation Performance and Milk Fatty Acid Profilementioning
confidence: 97%
“…The spectra were analyzed for background correction using machine-specific manufacturer software. The metabolites were identified using previous knowledge on the 1 H NMR spectra of cow milk [25][26].…”
Section: Introductionmentioning
confidence: 99%